ANALISIS FAKTOR-FAKTOR FUNDAMENTALSERTA PENGARUHNYA TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN YANG GO PUBLIK DI BURSA EFEK INDONESIA - Effendi, David (Journal of Accounting and Strategic Finance, 2010)
Based on the phenomena, this research is trying to test and prove whether the liquidity ratio, leverage, profitability ratio, also the company age have some influences to the voluntary revelation of financial report.The populations of this research are fourteen food and beverage companies, with the research sample since 2005 until 2008 with the purposive sampling method. The analysis method used is the multiple linear regression comply with the formulation of the problems and research hypotheses. This research concludes that liquidity ratio (X1), leverage ratio (X2), profitability ratio (X3) and company age (X4) do not influence to the voluntary revelation (Y), so that the hypotheses of this research that : “there is a positive influence between liquidity ratio, leverage ratio, profitability ratio, and company age toward the completion voluntary revelation of the company financial report” the truth is not tested.   Keywords : Liquidity Ratio, Leverage Ratio, Profitability Ratio, Company Age, Voluntary Revelation